The Influence Of Interest In Learning On The Learning Outcomes Of Grade Iv Students In The Eyes Maths Lessons - Fadliyana, Annisa; Ardianti, Sekar Dwi; Santoso, Denni Agung (JPMI (Jurnal Pendidikan Matematika Indonesia), 2023)
The purpose of this study was to determine the influence of interest in learning on the learning outcomes of grade IV students in mathematics subjects. This research is a type of quantitative research with ex-post facto methods. The instruments used are observation sheets and interview sheets for pre-research then for research, namely questionnaire sheets, test sheets and documentation. The sample in this study was grade IV students of Al-Maraghy with a total of 36 students. The data analysis techniques used are normality test, linearity test as an analysis prerequisite test, simple linear regression test as a hypothesis test. The results showed that there was a positive and significant influence between learning interest on the learning outcomes of grade IV students in mathematics subjects with the influence of learning interest on learning outcomes by 12.1% and 87.9% influenced by other variables that were not studied.